Factors supporting Indonesia's economic growth in 2004 – 2012 - Merio Primary (Institute of Accounting Research and Novation (IARN), 2021)
In Indonesia, GDP growth in 2010 – 2012 continued to increase, despite the economic crisis in Europe. Therefore, to study Indonesia's economic growth, it can be observed from the factors that influence economic growth in Indonesia. The purpose of this study was to determine and analyze the effect of household consumption, the effect of state spending, the effect of values, the effect of export values ​​and the effect of the Euro-rupiah exchange rate on Indonesia's economic growth in 2004-2012. The variables used in this study are gross domestic product (GDP), household consumption expenditures, government expenditures, investment, exports and imports of Indonesia. The dependent variable in this study is gross domestic product (Y), while the independent variable is household consumption expenditure (X1). From this study, it was found that household consumption had a significant positive effect on Indonesia's gross domestic product (GDP) in 2004 – 2012. The regression coefficient of the household consumption variable was 2.080 with a t-value of 2.341 > t-table (1.697) with a p-value = 0.026 < α = 0.05. Government expenditure has a significant positive effect on Indonesia's gross domestic product (GDP) in 2004 – 2012. The regression coefficient of the variable government expenditure is 1.237 with t count = 2.602 > t table (1.697) and p value = 0.014 <α = 0.05 .